Matrix metalloproteinase-9 Gene-1562C>T Gene Polymorphism and Coronary Artery Disease in the Chinese Han Population: A Meta-Analysis of 5468 Subjects - Li, Yan-Yan; Yang, Xin-Xing; Zhou, Yan-Hong; Gong, Ge; Geng, Hong-Yu; Kim, Hyun J.; Zhou, Chuan-Wei; Qian, Yun; Wang, Xiang-Ming; Wu, Jun (Frontiers in Physiology, 2016)
Background: Multiple studies indicate that the matrix metalloproteinase-9 (MMP-9)-1562C>T gene polymorphism may be associated with an increased risk of coronary artery disease (CAD) in the Chinese Han population. However, a clear consensus has yet to be established. Objective and methods: A meta-analysis of 5468subjects from10separate studies was performed to explore the possible relationship between theMMP-9-1562C>T gene polymorphism and CAD within the Chinese Han population. Pooled odds ratio (ORs) for the association and the corresponding 95% confidence intervals (CIs) were evaluated by a random or fixed-effect model. Results: Our analysis confirms the association between the MMP-9 -1562C>Tgene polymorphism and an increased risk of CAD within the Chinese Han population under allelic (OR: 1.60, 95% CI: 1.25-2.04, P=0.0002),recessive (OR:3.05, 95% CI: 1.67-5.56, P=0.0003), dominant (OR:2.23, 95% CI:1.49-3.35, P=0.0001), homozygous(OR:3.41, 95% CI: 1.87-6.23, P<0.0001), heterozygous (OR:2.03, 95% CI:1.40-2.93, P=0.0002),and additive genetic models(OR:1.78, 95% CI:1.33-2.39, P<0.0001). Conclusions: In the Chinese Han population, the MMP-9 -1562C>T gene polymorphism is correlated with an increased risk of CAD. Therefore, Han Chinese carriers of the -1562T allele may be at an increased risk of CAD.